Analysis of Steam Needs at Stelilizer Station With 80 Minutes at Pt Socfindo Seunagan Palm Oil Factory - Asri Refendi Refendi; Sulaiman Ali; Joli Supardi (Jurnal Inotera, 2022)
The process of making palm oil fresh fruit bunches (FFB) into crude palm oil (CPO) goes through many processing sessions. The processing steps were tried at several stations, including reception stations, sorting stations, sterilizer stations, thresher stations, digester and press stations, and clarification stations. One very useful process lies in the sterilizer station. The quality of the resulting CPO, one of which depends on the boiling process at the sterilizer station. FFB boiling process at PT. Socfindo seunagan uses a triple peak system, with pressures near 2.5 to 3 bar. The boiling process is tried for 80 to 85 minutes. The processing time, which takes so long, will ripen the fruit to the bottom